Process-based Strategic Planning - Grünig, Rudolf (Springer, 2017)
A company's strategies define its future direction, specifying not only target market positions for many years to come, but also the key competitive advantages both at the level of market offers and of resources. Developing future strategies is an important and complex task, which is the core issue in this book. After a short introduction to strategic planning, a heuristic process for determining future strategies is presented. This process is divided into seven steps, and for each of these steps, detailed recommendations for problem-solving are provided and illustrated through many concrete examples. The new edition is improved and contains new material.